The impact of protein standardisation with liquid or powdered milk permeate on the rheological properties of skim milk concentrates. (August 2021) - Tsermoula, Paraskevi; Drapala, Kamil P.; Joyce, Aoife M.; Hoare, Kate; Crowley, Shane V.; O'Mahony, James A.
Abstract: The objective of this study was to determine the effect of mineral addition during standardisation on colloidal and rheological properties of skim milk on concentration. For that purpose, solubility, ionic strength and ionic calcium activity of milk permeate were determined and skim milk was standardised with either lactose or milk permeate (in powder or reconstituted form). Results indicated that milk permeate contains mineral complexes that alter the ionic equilibrium of skim milk and standardisation with permeate powder has the potential to decrease casein micelle size and integrity. Apparent viscosity of the concentrates demonstrated that skim milk standardised with milk permeate powder had the highest viscosity, followed by that standardised with reconstituted milk permeate or lactose. These novel results demonstrate that the physical state of minerals in milk permeate influence the physicochemical properties of skim milk and thereby affect viscosity of resultant concentrates.